Combined heat and power system for stoves with thermoelectric generators. (1st January 2017) - Montecucco, A.; Siviter, J.; Knox, A.R.
Graphical abstract: Highlights: Stoves are used to cook and heat in developing countries and remote locations. This article presents a thermoelectric combined heat and power system for stoves. This working system comprises of thermo-mechanical assemblies and power electronics. It produced 600 Wth and 27 Wel during 2-h of use. Abstract: Solid-fuel stoves are used in developing countries, remote locations, and in general more commonly due to convenient fuel cost for space heating. The possibility of also using the stove heat to heat water and produce electricity represents an added benefit. This work presents an application of thermoelectric generators to a solid-fuel stove to concurrently charge a lead-acid battery and transfer heat to water for heating or household use. The feasibility of the proposed CHP system is demonstrated for a common solid-fuel stove. This system produces an average of 600 W th and 27 W el ( 42 W el peak) during a 2-h long experiment in which the TEG efficiency is around 5% and the MPPT efficiency of the power converters used is demonstrated.